Endovenous Laser Ablation for Treatment of a Partially Thrombosed Proximal Great Saphenous Vein - Luca Spinedi; Hans Stricker; Daniel Staub; Heiko Uthoff (Case Reports in Vascular Medicine)
Introduction. Superficial vein thrombosis of the great saphenous vein near to the saphenofemoral junction is generally treated with anticoagulation or surgically. Report. We present the case of a 70-year-old man with varicosities and a partially thrombosed great saphenous vein near to the saphenofemoral junction, treated with endovenous laser ablation of the great saphenous vein. Discussion. The case illustrates an alternative treatment option for superficial vein thrombosis of the great saphenous vein, which permits avoiding a prolonged anticoagulation or surgical procedure.